[RETRACTED] Enhancing Pre-Service Mathematics Teachers’ Numeracy Through Integrated STEAM Geometry: Bridging Creativity and Mathematical Precision - Fenyvess, Jana; Sylvenia, Norvelyn Theodora; Siskawati, Rina Hafizah; Haerul, Syam (SMARTH: Journal of Mathematics Education and Learning, 2025)
RETRACTION NOTICE This article has been formally retracted by the Editorial Board of SMARTH: Journal of Mathematics Education and Learning. Following a formal complaint and subsequent investigation, it was determined that this article involved the unauthorized use of an individual’s name and institutional affiliation. The individual concerned confirmed that they had no involvement in the authorship, review, or approval of this manuscript. This constitutes a serious breach of publication ethics, specifically authorship misrepresentation. In accordance with the guidelines of the Committee on Publication Ethics (COPE), the article has been withdrawn to maintain the integrity of the scholarly record. The content of this article should not be considered reliable and should not be cited. The Editorial Board regrets that this issue was not identified prior to publication and has implemented additional measures to strengthen the editorial and verification process.